Penurunan Kadar TSS, COD, BOD Dan Fosfat Dalam Pengolahan Limbah Cair Industri Kecil Laundry Menggunakan Kombinasi Teknologi Aerasi Dan Fitoremediasi Tanaman Enceng Gondok (Eichhornia Crassipes) - Bagas Tri Pamungkas; Fairuz Salma Afifah; Nur Ilman Ilyas; Dhonny Suwazan (Prosiding Sains dan Teknologi, 2022)
The research began with plant acclimatization, continued with RFT testing, and core research, as well as laboratory testing of wastewater quality before and before the process. Then an analysis was carried out based on the results of laboratory tests. This research uses pump circulation for two reactors, namely aeration reactor and phytoremediation reactor and the detention time of wastewater in the reactor is 7 days. From the results of the study, it was found that the combination of aeration and phytoremediation technology showed a TSS parameter removal efficiency level of 79.56% or a decrease of 18.3mg/L, a COD parameter of 67.87% or a decrease of 169mg/L and a decrease in BOD parameter of 51mg/L. with an effectiveness of 68%. Meanwhile, the Phosphate (PO4) parameter decreased by 0.08 mg/L or the removal effectiveness level was 66.67%. Keywords: Laundry, Aeration, Phytoremediation, TSS, COD, BOD, Phosphat